PERSEPSI TERHADAP LINGKUNGAN - Ai Siti Patimah; Arundati Shinta; Amin Al Adib (Jurnal Psikologi, 2024)
The problem that most often arises in various environmental issues is people's lack of concern for cleanliness, environmental care and conservation. This indifference originates from his perception when faced with this distressing situation. People who do not care will perceive that the situation is bad but can still be tolerated. Therefore the behavior is not to just leave the situation. However, when an individual perceives that the situation is extremely bad, he or she becomes stress. This unacceptable situation motivates him or her to cope it. When successful in coping stress, the individual is free from stress. On another occasion, if the individual finds a situation that is just as bad, he or she will repeat the behavior that was successful in overcoming the bad situation. On the other hand, when an individual feels unable to cope with stress, he will still feel stressed when faced with a similar bad situation. Stressful behavior may include getting angry, slamming things, setting fires, throwing bombs, and so on. It is hoped that this perception process can provide input for policy makers and stakeholders so that the bad situation facing society can be overcome.